Digital Currencies Reshaping Cross-Border Trade: Opportunities, Challenges, and Strategic Frameworks: Mata Uang Digital Membentuk Kembali Perdagangan Lintas Batas: Peluang, Tantangan, dan Kerangka Kerja Strategis - Gabriel Ayodeji Ogunmola (Universitas Muhammadiyah Sidoarjo, 2025)
Digital currencies have merged with the international trade, creating a paradigm shift towards or even complete change in cross border transactions dynamics. In this extensive research study, the complex relation between digital currencies and international trade are explored, for the opportunities are as plentiful as the obstacles. I have included a comprehensive analysis of empirical evidences and case studies to demonstrate how digital currencies can positively affect cross border transactions. Consequently, the findings specifically point out the advantages of enabling enhanced efficiency, achieving cost reduction, facilitation of financial inclusion, and transparency and traceability in trade brought about by digital currencies. However, troublesome regulatory intricacies, apprehensions of security, potential system switching, adverse implications for the stability of the economy and the financial system and the volatility of exchange rates present substantial hurdles. For this reason, this piece of research highlights the need to develop synergistic regulatory frameworks, apposite risk management methods, and proactive actions to handle the acerbic nature of digital currencies in the party of global trade. We propose a fundamental framework for understanding and solving the emerging problems and opportunities in the area in the global commerce, as a result of the ongoing digital currency revolution. Highlights: Digital currencies reshape international trade, enhancing efficiency and reducing costs. Regulatory challenges, security risks, and volatility hinder seamless global adoption. A strategic framework is needed for risk management and regulatory synergy. Keywords: Digital Currency, International Trade, Cryptocurrencies, Central Bank Digital Currencies (CBDC), Cross-Border Transactions